Self-Efficacy and School Support on Students' Behavioral Intention to Adopt Learning Technologies: The Mediating Roles of TPACK and Perceived Usefulness - Geby Putri Maharani; Alifiya NFH; Ridwan Daud Mahande; Soeharto; Nguyen Van Son (Academic Bright Collaboration, 2026)
Purpose – Despite the increasing integration of digital technologies in higher education, students’ actual adoption remains inconsistent. Prior studies have predominantly relied on the Technology Acceptance Model (TAM), with limited attention to pedagogical technological competence and the interaction between psychological and institutional factors. This study aims to examine the influence of Self-Efficacy and School Support on students’ Behavioral Intention to use educational technology, with the mediating roles of Perceived Usefulness and Technological Pedagogical Content Knowledge (TPACK).Methods – A quantitative approach with a cross-sectional survey design was employed. Data were collected from 330 university students in South Sulawesi, Indonesia, using an online questionnaire and analyzed through Partial Least Squares Structural Equation Modeling (PLS-SEM).Findings - The results show that Self-Efficacy significantly influences TPACK (β = 0.751, p < 0.001) and Perceived Usefulness (β = 0.798, p < 0.001), while School Support significantly affects TPACK (β = 0.174, p < 0.001). Furthermore, TPACK (β = 0.603, p < 0.001) and Perceived Usefulness (β = 0.267, p < 0.001) significantly predict Behavioral Intention. Mediation analysis indicates that Perceived Usefulness (β = 0.213, p < 0.001) and TPACK (β = 0.105–0.453, p < 0.001) serve as significant mediators.Research implications – These findings emphasize the importance of enhancing students’ technological competence and strengthening institutional support systems to promote effective technology adoption. However, the study is limited to a specific regional context, which may affect generalizability.Originality – This study extends TAM–TPACK integration by introducing a dual mediation framework that simultaneously examines psychological (Self-Efficacy) and institutional (School Support) factors in university students, highlighting the mediating roles of Perceived Usefulness and TPACK in technology adoption..